PERAN PENYULUH DALAM PENERAPAN INDONESIAN SUSTAINABLE PALM OIL (ISPO) PADA PETANI KELAPA SAWIT SWADAYA DI KABUPATEN KAMPAR - Nurhaliza Nurhaliza; Rosnita Rosnita; Novia Dewi (JSEP (Journal of Social and Agricultural Economics), 2021)
Riau Province is the largest palm oil producing province and Indonesian Sustainable Palm Oil (ISPO) is one aspect that must be applied by farmers in increasing the competitiveness of the palm oil business they manage. This study aims to analyze the role of extension workers in implementing ISPO in Kampar District. Multistage area sampling is a sampling method used in research. The study population consisted of independent oil palm farmers with a total sample of 90 independent smallholders. Data were analyzed using descriptive analysis and a Likert scale. The results of the study illustrated that the counseling in Kampar District was not going well. On average, the role of extension is lacking in providing education, dissemination, information, facilitation, consultation, supervision and monitoring evaluation to independent smallholders so that farmers have not been able to apply the principles of ISPO (Indonesian Sustainable Palm Oil)